Corticosteroid Effects and Administration Time Difference on Mice Model of Biliary Atresia - Bagus Setyoboedi, Bagus
Abstract Corticosteroid therapy (steroid) has evolved into a commonly selected therapy after portoenterostomy therapy and is believed to improve clinical outcomes in biliary atresia (BA). This study aims to evaluate the effects of corticosteroid administration and its administration time on innate immune response, the changes from innate to non-self adaptive immunity, non-self adaptive immunity, and self-adaptive immunity, as well as a biliary obstruction on animal models of biliary atresia. This study utilized a randomized multiple factorial and posttest-only control group designs on newborn Balb/c mice as the animal models. Forty-four mice were randomly categorized into two groups, i.e., the experimental and control groups. All mice underwent the examination of several liver variables, liver histopathology, as well as bile ducts after the termination process. Univariate Ttest and factorial MANOVA were employed for the data analysis. If the data were not normally distributed, the analysis could be carried out using the median and interquartile range, MannWhitney U test, and Kruskal-Wallis test. Dexamethasone administration, Rhesus Rotavirus (RRV) induction, and pain duration after RRV exposure provided interaction effects towards CD68 expression with the significance values as follows: day 7= (0.01), day 14 = (0.001), and day 21 = (0.035); CD39 expression on day 7 (0.01), day 14 (0.001), and day 21 (0.001); CD4 expression on day 7 (0.001), day 14 (0.018), and day 21 (0.018); CD8 expression on day 7 (0.001), day 14 (0.018), and day 21 (0.014); B cell expression on day 7 (0.001), day 14 (0.002), and day 21 (0.018); ANCA expression on day 7 (0.012), day 14 (0.05), and day 21 (0.001). After RRV induction, the immune response on animal models of biliary atresia increases. Dexamethasone administration on day 7 after RRV induction provides the most effective effects on immune response decrease.